Banking Financial System Stability Analysis - Anindita Neng Pda (Ridwan Institute, 2021)
The purpose of this study was to determine the effect of the competition’s level, the level of credit growth on financial system stability. The method in this study is panel data regression with three approaches, namely common effect, fixed effect and random effect. The data used is monthly time series data starting from June 2015 to June 2018 and cross section data from all types of commercial banks covering four types of banks based on the distribution of BUKU (Business Commercial Banks). The data obtained from the official website of Bank Indonesia, the Financial Services Authority, the internet and other references sourced from literature, literature studies, scientific journals, supporting books and various other sources related to research. The results of this study indicate that the Fixed Effect Model is the best model for further estimation based on the results of the Chow test and Hausman test. These results also explain that the Bank's Competition Level has a positive effetc but not significant on bank stability. Meanwhile, credit growth has a negative impact and significant on bank stability, and profit sharing financing has a positive impact and significant on bank stability